PENGARUH PENGAJARAN DIALOGIS DAN PENALARAN TERHADAP KEMAMPUAN BERPIKIR KRITIS MAHASISWA PENDIDIKAN AKUNTANSI UNS - Dzikra Lulu Azzahra; Elvia Ivada (STKIP Subang, 2026)
This quantitative research analyzes the e fects of dialogic teaching and reasoning on the critical thinking ski ls of Accounting Education students from the 2023 and 2024 cohorts. Utilizing a Stratified Random Sampling technique, a sample of 117 respondents was obtained. Data were colected via questionnaires and analyzed using multiple linear regression with SPSS. Partial testing indicates that both dialogic teaching and reasoning have positive and significant e fects on critical thinking. Simultaneously, both variables contribute 61.2% to explaining the variation in students' critical thinking capacity. However, descriptive analysis reveals an evaluative note: students' limitations in coordinating ideas and variable reasoning directly imply lower precision in drawing accounting conclusions. Therefore, accounting instruction should not merely focus on the courage to argue, but rather on strengthening the capacity for synthesis and precise scientific reasoning. The limitation of this study lies in the potential for subjectivity bias due to the reliance on self-report instruments.